2016
DOI: 10.3390/v8100272
|View full text |Cite
|
Sign up to set email alerts
|

A Viral Noncoding RNA Complements a Weakened Viral RNA Silencing Suppressor and Promotes Efficient Systemic Host Infection

Abstract: Systemic movement of beet necrotic yellow vein virus (BNYVV) in Beta macrocarpa depends on viral RNA3, whereas in Nicotiana benthamiana this RNA is dispensable. RNA3 contains a coremin motif of 20 nucleotides essential for the stabilization of noncoding RNA3 (ncRNA3) and for long-distance movement in Beta species. Coremin mutants that are unable to accumulate ncRNA3 also do not achieve systemic movement in Beta species. A mutant virus carrying a mutation in the p14 viral suppressor of RNA silencing (VSR), unab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 33 publications
(80 reference statements)
2
30
1
Order By: Relevance
“…The mechanisms by which other RNA viruses maintain the stability of their transcripts during infection have not been wellcharacterized. Interestingly, XRN1 stalling at specific sites in viral RNAs has also been noted for several segmented plant RNA viruses (19,20). Thus, we hypothesized that segmented RNA viruses infecting mammalian systems might have also evolved RNA structure-based strategies to stall XRN1 as part of their approach for effective host interaction.…”
mentioning
confidence: 90%
“…The mechanisms by which other RNA viruses maintain the stability of their transcripts during infection have not been wellcharacterized. Interestingly, XRN1 stalling at specific sites in viral RNAs has also been noted for several segmented plant RNA viruses (19,20). Thus, we hypothesized that segmented RNA viruses infecting mammalian systems might have also evolved RNA structure-based strategies to stall XRN1 as part of their approach for effective host interaction.…”
mentioning
confidence: 90%
“…Exoribonuclease resistance as a means to generate non-coding RNA from larger precursors is an emerging theme in virology (21)(22)(23)(24)26). We have found that exoribonuclease-blocking sequences from plant-infecting dianthoviruses are authentic xrRNAs, generating viral non-coding RNAs in a process dependent on a specific but dynamic threedimensional RNA fold.…”
Section: Discussionmentioning
confidence: 99%
“…Exoribonuclease resistance conferred by RNA structure may be a more common mechanism than hitherto anticipated, and recent studies have identified putative xrRNAs in several virus families. A conserved sequence that blocks 5¢à3¢ exoribonucleolytic decay was recently found in the 3¢UTR of plant-infecting benyviruses and cucumoviruses; both have multipartite positive-sense RNA genomes (23,24,31). Moreover, Xrn1 is confounded by RNA elements in the 5¢UTRs of hepaci-and pestiviruses (21), as well as by a G-rich sequence structure in the N mRNA of Rift Valley fever virus, and multiple RNA structures in ambisense-derived transcripts of arenaviruses (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During infection of Beta macrocarpa by Beet necrotic yellow vein virus (BNYVV), a member of the Benyviridae family and Benyvirus genus 22 , a non-coding RNA is produced from BNYVV RNA3 23 . This RNA, and in particular the "core" sequence it carries, has been shown to be necessary for long-distance movement by the virus and can be produced by action of either yeast Xrn1 or plant XRN4 [24][25][26] . A highly conserved 20 nucleotide (nt) sequence within the core, termed "coremin", plays an important role in allowing for systematic infection by BNYVV RNA3 in Beta macrocarpa 23 .…”
Section: Introductionmentioning
confidence: 99%